Intrathecal Infusion of Haploidentical Nondonor Lymphocytes for Central Nervous System Leukemic Relapse After Haploidentical Hematopoietic Stem Cell Transplantation. Issue 2 (March 2018) - Mayumi, Azusa; Sawada, Akihisa; Ioi, Aya; Higuchi, Kohei; Shimizu, Mariko; Sato, Maho; Yasui, Masahiro; Inoue, Masami
Abstract : Leukemic relapse in the central nervous system (CNS) after conventional treatment is associated with a poor prognosis. The effectiveness and safety of IV infusion of human leukocyte antigen (HLA)-mismatched lymphocytes for leukemia, and intrathecal (IT) infusion of HLA-mismatched lymphocytes for cerebrospinal fluid (CSF) dissemination of medulloblastoma have been reported. A 13-year-old girl (HLA-A31 + ) was diagnosed as relapsing from Philadelphia chromosome–positive acute leukemia in the CNS after receiving chemotherapy, tyrosine kinase inhibitors, haploidentical hematopoietic stem cell transplantation (HSCT) from her father (HLA-A31 − ), and craniospinal irradiation. We performed an IT infusion of haploidentical lymphocytes from her mother. Peripheral blood mononuclear cells obtained from her mother (HLA-A31 + ) were administered by IT infusion weekly. Examination of CSF 1 week after first IT showed that lymphocyte counts had increased markedly and the breakpoint cluster region/abelson -bearing cells had disappeared. Furthermore, CD3 + T cells in the CSF were negative for HLA-A31, and expressed high HLA-DR. These results indicate the infused non–HSCT-donor lymphocytes did not survive, and that the HSCT donor(father)–derived lymphocytes migrated to the CSF and were activated. The patient showed partial remission for 2 months following this therapy. Serious adverse reactions and graft versus host disease were not observed. To control leukemic CNS dissemination, haploidentical nondonor lymphocytes might contribute to a graft versus leukemia effect.